Fibro-osseous pseudotumour of the digit—a diagnostic challenge. Issue 5 (1st June 2020) - Rela, Mariam; Bantick, Giles
Abstract: A 60-year-old right-hand dominant woman presented to the emergency department with a 3-week history of pain and swelling in her right thumb. The X-ray showed evidence of erosion at the tip of the distal phalanx. Her initial management included surgical debridement with bone biopsies and intravenous antibiotics. The initial working diagnosis was a soft tissue infection of the thumb tip, causing osteomyelitis of the distal phalanx. The X-ray findings also raised the suspicion of a possible bone tumour. She was treated as having osteomyelitis and attended ambulatory care for daily intravenous antibiotics for 2 weeks. Initial histology was reported as a spindle cell tumour; however, following discussion at the sarcoma MDT, a diagnosis of a fibro-osseous pseudotumour of the digit was made. This is a benign lesion that was managed non-operatively in this patient. This case emphasises the importance of considering all differential diagnoses, even in a common presentation.